Implementation of Competition Law In Cooking Oil Price Trading For Public Interest - Dominikus Dalu Sogen (Publikasi Indonesia, 2023)
This study discusses the implementation of competition law in the trading system of cooking oil prices for the public interest in Indonesia. Business competition law aims to encourage healthy competition between business actors in the market, including in the cooking oil sector. However, the implementation of this law still faces various challenges, especially related to suboptimal law enforcement and lack of public understanding of consumer rights in the market. Through a literature study approach, this study discusses the concept of business competition law and its role in encouraging healthy competition in cooking oil price trading. The results showed that the implementation of competition law in cooking oil price trading can provide benefits for the public, such as more affordable prices and better product quality. However, this can only be achieved if the government, business actors, and the community work together to improve understanding and enforcement of business competition law. In conclusion, the implementation of business competition law in cooking oil price trading can have a positive impact on the public interest if carried out properly and optimally. Therefore, an active role from all relevant parties is needed to ensure the successful implementation of this law.